The differentiated CSR activities and corporate value - Kim, Sang Il; Kim, Kyung Tae (Asian Review of Accounting, 2021)
Purpose: Corporate social responsibility (CSR) index represents attributes of firms that are differentiated. The purpose of this paper is to investigate the impacts of differentiated CSR, CSRS (strategic CSR activities) and CSRD (defensive CSR activities) on R&D expenditure and its effectiveness on firm values. Design/methodology/approach: The sample includes 1,388 firm-year observations for 2004–2015 of listed firms on the Korean Stock Exchange (KSE) whose CSR measures, KEJI (Korea Economic Justice Institute) index are available from the Citizens' Coalition for Economic Justice (2016). Findings: The results show that while CSRS is positively associated with R&D expenditure, CSRD is not. Further, development costs and its interaction term with CSRS positively affect firm values. Originality/value: This study provides an important reason to separate the attributes of the CSR in future empirical studies. The results imply that the study of effects of CSR on sustainable growth or firm values should focus on CSRS rather than CSR activities in general in future research.
Keywords: Defensive CSR; Firm value; R&D expenditure; Strategic CSR